UPAYA HUKUM TERHADAP PUTUSAN KPPU OLEH PANITIAN TENDER DALAM HAL DIPUTUS BERSALAH MELANGGAR PASAL 22 UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - DIAH RAHMAWATI, SH NPM. A.21208068, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2013)
AbstractOne form of action that could result in unfair competition is a conspiracy in the tender, which is one form of activity that is prohibited by Law No. 5 of 1999. The general principles to be considered in the tender are transparency, respect for money, open and effective competition, fair negotiation, accountability and assessment process, and non-discriminatory. Accordingly, the Act No. 5 of 1999 also prohibits conspiracy in tenders as outlined in Article 22 of Law No. 5 of 1999. This study aims to determine how the position and role of the tender committee in the case of bid rigging and how to remedy that may be filed by the tender committee against the decision of the Commission for Unfair using dogmatic normative juridical approach, the approach that is based on secondary data sources such as the rules laws and regulations, court decisions, legal theories and opinions of legal scholars terkenal.Kemudian of secondary data is then analyzed using qualitative methods-normative. Normative because this research starts from the legislation that exists as a norm of positive law. While the intended qualitative data obtained are then arranged systematically to further analyzed qualitatively in order to seek clarity issues to be addressed Based on the analysis it was found that in the case of competition, there are still drawbacks to the examination of the case law shows good competition at the time of the Business Competition Supervisory Commission and in terms of the presentation of legal remedy of appeal in the District Court.So to overcome these problems should be advised to revise the Act No. 5 of 1999 to provide firmness of independence because of the peculiar field of competition law, including the laws that govern the event.But if it was politically undesirable law a revision of Law No. 5 of 1999 then at least made a good form of regulations implementing government regulation or at least the Supreme Court Rules provides that at least in cases of anti-competition dimension of crimes that harm the state or the public as anti-competitive actions within the framework of the cartel, should use criminal law or the law of a special public event where the Commission as an investigator and prosecutor agencies, as well as for the case of anti-competitive strife dimension or a dimension businessmen consumer class action the Commission serves as a quasi judicial first level, where the Commissioner to